PENGARUH MEDIA LOTTO TERHADAP KEMAMPUAN MENGENAL KONSEP ANGKA ANAK USIA 5–6 TAHUN DI PAUD TUNAS HARAPAN SUKANANTI OGAN ILIR - Rahmah Handayani; Leny Marlina; Izza Fitri (Al-Mudarris, 2026)
This study examines the effectiveness of Lotto-based learning media in enhancing number concept recognition among children aged 5-6 years in early childhood education settings. Premilinary observations indicated that children experienced difficulties in identifying number symbols, sequencing numbers, and matching quantities with corresponding numerals due to limited instructional media and minimal use of interactive learning approaches. A quantitative one-group pretest-posttest design was employed involving 13 children selected through purposive sampling. Data were collected through observation, testing, and documentation, and analyzed using descriptive statistics and paired sample t-test. The results revealed an improvement in the mean score from 60.23 in the pretest to 80.38 in the posttest, indicating significant gains in early numeracy skills. Beyond statistical improvement, Lotto media facilitated play-based and interactive learning experiences, enabling children to actively engage with numerical concepts through visual and concrete-symbolic respresentations. The media supported meaningful learning by connecting abstract number symbols with tangible quantities, fostering motivation and conceptual understanding. This study contributes to early childhood numeracy pedagogy by demonstrating the instructional value of game-based learning media in promoting foundational number concepts. The findings suggest that Lotto media can be integrated into early childhood classrooms as an effective pedagogical tool to enhance numeracy learning and student engagement.